Airway transcriptomic profiling after bronchial thermoplasty. Issue 1 (18th February 2019) - Liao, Shu-Yi; Linderholm, Angela L.; Yoneda, Ken Y.; Kenyon, Nicholas J.; Harper, Richart W.
Background: Bronchial thermoplasty is a nonpharmacological, device-based treatment option for a specific population of severe asthmatic subjects, but the underlying mechanisms are largely unknown. The purpose of this study is to identify potential altered pathways by bronchial thermoplasty using a transcriptomic approach. Methods: Patients undergoing bronchial thermoplasty were recruited to the study, and a bronchial brushing sample was obtained before each bronchial thermoplasty session and sent for RNA sequencing. A variance component score test was performed to identify those genes whose expression varied after bronchial thermoplasty sessions. Differential gene expression meta-analysis of severe asthmatic subjects versus controls was performed using public repositories. Overlapping genes were included for downstream pathway and network analyses. Results: 12 patients were enrolled in our study. A total of 133 severe asthma cases and 107 healthy controls from the public repositories were included in the meta-analysis. Comparison of differentially expressed genes from our study patients with the public repositories identified eight overlapping genes: AMIGO2, CBX7, NR3C2, SETBP1, SHANK2, SNTB1, STXBP1 and ZNF853 . Network analysis of these overlapping genes identified pathways associated with neurophysiological processes. Conclusion: We have shown that bronchial thermoplasty treatment alters several gene networks that are important in asthma pathogenesis. These results potentially elucidate the disease-modifying mechanisms of bronchial thermoplasty and provide several targets for further investigation. Gene networks that are altered in the airway epithelium of asthmatic subjects after bronchial thermoplasty http://ow.ly/Ki6x30nbPSj